Leading Operational Risk Events For South African Banks: A Reputational Risk Perspective - Ferreira-Schenk, Sune (International Journal of Economics and Financial Issues, 2023)
Banks have been exposed to operational risk for decades. Therefore, there is a strong reason to believe that the exposure to operational risk will only increase in future due to improved transparency as required by regulators as well as the increased reliance on improved technological automation within banks in the digital area. The aim of this article was to identify the leading operational risk events that will most likely lead to reputational risk for South African banks. Primary data were collected from 417 depositors in Gauteng, South Africa, using a self-structured questionnaire where hypothetical operational risk events were employed. External fraud had the highest reputational risk rating, followed by execution and delivery. Six out of the eight events, therefore, were considered severe in terms of the likelihood that depositors will withdraw. Seven out of the eight events, therefore, were considered severe in terms of the percentage of funds that depositors will withdraw. Also, seven out of the eight events were considered severe in terms of the likelihood of creating a negative perception in the minds of depositors. The majority of research in this area has stemmed from developed countries. The significant difference between previous research in the developed regions and South Africa lies in the absence of a deposit insurance scheme in the South African banking sector. Operational risk events that might be severe in developed countries might even be more severe in the South African context without proper banking insurance protecting depositors. Therefore, the novelty of this article lies in the contribution towards empirical evidence from one of the most sophisticated and promising emerging markets by identifying the most severe operational events on the reputational risk for banks.